La reacción ante el Profeta como respuesta a la palabra de Dios en Jeremías 26 - Pardo Izal, José Javier (Estudios eclesiásticos, 2007)
The Sermon against the Temple whose content can be read in Jr 7,1-8,3, constitutes one of the pillars of Jeremiah’s prophetic utterance. This discourse was probably one of the most important events that originated the movement against the Prophet. Chapter 26 takes up this event and presents it as a narrative thread of the whole second part of the book, Jr 26-45. A literary study of this narrative, in comparison with Jr 7, illuminates the different theological perspectives. The opposition to the prophet doesn’t reject the divine offer; rather it supposes a renovation, because the prophetic mission is actually a proposal for a dialogue that engenders freedom among the people. This freedom is possible because Yahweh could repent of his pronounced word. The theme continues in Jr 36 where people’s rejection and God’s proposition culminate in the written word.